Complete and assembled genome sequence of an NDM-9- and CTX-M-15-producing Klebsiella pneumoniae ST147 wastewater isolate from Switzerland. (June 2018) - Nüesch-Inderbinen, Magdalena; Zurfluh, Katrin; Stevens, Marc J.A.; Stephan, Roger
Abstract: Objectives: Carbapenem-resistant Klebsiella pneumoniae have emerged worldwide and represent a major threat to human health. Here we report the genome sequence of K. pneumoniae 002SK2, an NDM-9- and CTX-M-15-producing strain isolated from wastewater in Switzerland and belonging to the international high-risk clone sequence type 147 (ST147). Methods: Whole-genome sequencing of K. pneumoniae 002SK2 was performed using Pacific Biosciences (PacBio) single-molecule, real-time (SMRT) technology RS2 reads (C4/P6 chemistry). De novo assembly was performed using Canu assembler, and sequences were annotated using the NCBI Prokaryotic Genome Annotation Pipeline (PGAP). Results: The genome of K. pneumoniae 002SK2 consists of a 5.4-Mbp chromosome containing bla SHV-11 and fosA6, a 159-kb IncFIB(K) plasmid carrying the heavy metal resistance genes ars and sil, and a 77-kb IncR plasmid containing bla CTX-M-15, bla NDM-9, bla OXA-9 and bla TEM-1 . Conclusions: Multidrug-resistant K. pneumoniae harbouring bla NDM-9 and bla CTX-M-15 are spreading into the environment, most probably via wastewater from clinical settings.